Neoadjuvant endocrine therapy for luminal breast tumors: State of the art, challenges and future perspectives. (January 2023) - Sirico, Marianna; Virga, Alessandra; Conte, Benedetta; Urbini, Milena; Ulivi, Paola; Gianni, Caterina; Merloni, Filippo; Palleschi, Michela; Gasperoni, Marco; Curcio, Annalisa; Saha, Debjani; Buono, Giuseppe; et al.
Abstract: Neoadjuvant endocrine treatment (NET) associates to satisfactory rates of breast conservative surgery and conversions from inoperable to operable hormone receptor-positive (HR+)/HER2-negative breast cancer (BC), with less toxicities than neoadjuvant chemotherapy (NACT) and similar outcomes. Hence, it has been proposed as a logical alternative to NACT in patients with HR+/HER2- BC candidate to a neoadjuvant approach. Nevertheless, potential barriers to the widespread use of NET include the heterogeneous nature of patient response coupled with the long duration needed to achieve a clinical response. However, interest in NET has significantly increased in the last decade, owing to more in-depth investigation of several biomarkers for a more adequate patient selection and on-treatment benefit monitoring, such as PEPI score, Ki67 and genomic assays. This review is intended to describe the state-of-the-art regarding NET, its future perspectives and potential integration with molecular biomarkers for the optimal selection of patients, regimen and duration of (neo)adjuvant treatments. Highlights: Neoadjuvant endocrine therapy (NET) is still underrated and scarcely used. Biomarkers are needed to identify best candidates for NET. Ki67 on-treatment or post-surgery can be useful for therapeutic guidance. Gene expression assays are a potential tool for tailoring neoadjuvant treatments. New target agents associated to NET may favour its use overchemotherapy.